Comprehensive insights into colistin and colistin resistance: updated regulations and policies on colistin usage and alternative strategies for mitigation and prevention of colistin resistance - Zine El abidine Bzazou El Ouazzani; Laila Reklaoui; Monsif El Madany; Houda Benaicha; Said Barrijal (Novel Research in Microbiology Journal)
The increase in antimicrobial resistance (AMR) has a significant impact on healthcare, leading to longer hospital stays and higher economic costs. This is primarily caused by the over and inappropriate use of antibiotics. Microorganisms have developed various mechanisms to combat the effects of antibiotics, including modifying their genetic material to evade the drugs' harmful effects. Colistin disrupts bacterial cell membranes by interacting with lipopolysaccharides (LPS), causing cell death. Currently, colistin is regarded as a last-resort antibiotic for treating infections caused by Gram-negative bacteria (GNB). Overuse of colistin in animal feed and human medicine has led to the appearance of genetic mutations and the acquisition of mobile colistin resistance (mcr) genes associated with colistin resistance. The rapid emergence of the plasmid colistin-resistant gene further complicates treatment strategies, emphasizing the pressing need for improved management and development of novel antimicrobial agents. Thus, gaining an understanding of the mechanisms behind colistin resistance and surveying its global prevalence are crucial steps in managing the growing menace of antimicrobial resistance and safeguarding the effectiveness of existing antibiotics. This review aimed to provide an in-depth and up-to-date overview of the colistin antibiotic, detailing its updated modes of action and associated side effects. Additionally, it delves into various mechanisms of resistance to colistin, advanced susceptibility test methods used for detecting colistin resistance, and the challenges associated with these techniques. Furthermore, the review examines the risk factors contributing to the development of colistin resistance, highlights updated regulations and policies governing colistin usage, and puts forth innovative strategies for addressing this resistance.